Biocompatibility and osteopromotor factor of bovine integral bone—a microscopic and histometric analysis - Bassi, Ana Paula Farnezi [UNESP]; Bizelli, Vinícius Ferreira [UNESP]; Consolaro, Renata Bianco; de Carvalho, Paulo Sérgio Perri (AME Publishing Company, 2021)
Background: The objective of this study was to evaluate the biological properties, biocompatibility, and osteopromotor factor of integral bone of bovine origin implanted in critical defects of rat calvaria and the subcutaneous plane of rats. Methods: The study was divided into two stages. For the first stage, 24 rats were divided into two groups of 12 animals: group GC, in which the critical defect was filled only by clot, and group GO, in which the defect was filled with particulate biomaterial, and the analysis performed at 30 and 60 days postoperatively. For the second stage, 16 rats were divided into two groups of eight animals: the GOP group, in which the biomaterial in its particulate form was inserted in the subcutaneous plane, and the GOB group, in which the block biomaterial was inserted in the subcutaneous; and the analysis performed at 15 and 45 days postoperatively. Results: The histological and histometric results of the calvaria demonstrated that the biomaterial induced a foreign body reaction over the entire length of the defect and around the particles and was not able to induce bone neoformation. Statistically, no difference was observed for the time, biomaterial, and time × biomaterial parameters (P>0.05). Subcutaneous microscopic examination of the pieces obtained at 15 days showed an inflammatory reaction around the particles of the material with the presence of giant cells and at 45 days, and a reduction in the inflammatory reaction and presence of fibrous connective tissue around the particles was observed with the presence of giant cells, and for the block biomaterial, connective tissue was present in the trabecular spaces. There was no evidence of ectopic bone formation. Conclusions: The biomaterial, despite being biocompatible, do not promote bone neoformation.
Keywords: Biocompatibility; Guided bone regeneration; Integral bone; Osteopromotor; Xenogenic